Comparison of Maternal and Fetal Outcome in Pregnant Women with BMI ≤ 25 KG/M2 and > 25 KG/M2 at Tertiary Care Hospital, Karachi - Asma Ali Depar, Hina Habib, Nazneen Hameed, Hiba Arshad Shaikh, Aisha Altaf, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of maternal and fetal outcome in pregnant women with BMI ≤ 25 kg/m2 and > 25 kg/m2 at Tertiary Care Hospital, Karachi. Study Design: Descriptive study. Place and Duration: Study was conducted at Department of Gynaecology and Obstetrics, Aga Khan University Hospital. Duration was six months after approval from 7th November, 2019 till 7th May 2020. Subjects and Methods: Data was prospectively collected from patients after taking a verbal consent. 201 patients who met the diagnostic criteria were included. Brief history was taken and demographic information was entered in the performa. Quantitative data was presented as simple descriptive statistics giving mean and standard deviation and qualitative variables was presented as frequency and percentages. Effect modifiers were controlled through stratification. Post stratification chi square test and t test was applied taking p-value of ≤0.05 as significant. Results: A total of 201 patients were included in this study. Mean age in < 25 kg/m2 and > 25 kg/m2 BMI groups in our study was 27.21±6.24 years and 26.48±8.41 years. Out of 90 patients with BMI < 25kg/m2, 12.2%, 1.1%, 1.1%, 8.9%, 16.7%, 16.7%, 1.1%, 1.1% and 1.1% had gestational diabetes postpartum hemorrhage, pregnancy induced hypertension, anemia, birth weight < 2500 gm, perinatal mortality, still birth and early neonatal death. Whereas out of 111 patients with BMI > 25kg/m2, 26.1%, 7.2%, 18%, 15.3%, 18.9%, 1.8%, 2.7% and 1.8% had gestational diabetes postpartum hemorrhage, pregnancy induced hypertension, anemia, birth weight < 2500 gm, perinatal mortality, still birth and early neonatal death. Conclusion: Obesity is a risk factor for maternal and fetal is evident from our study. Pre-pregnancy dietary counseling, regular physical activity, and a healthy lifestyle could help to reduce the incidence of gestational obesity and the incidence of perinatal complications as well. Keywords: Body Mass Index, Maternal Outcomes and Fetal Outcomes.